AmoA-Targeted Polymerase Chain Reaction Primers for the Specific Detection and Quantification of Comammox Nitrospira in the Environment - Pjevac, Petra; Schauberger, Clemens; Poghosyan, Lianna; Herbold, Craig W.; van Kessel, Maartje A. H. J.; Daebeler, Anne; Steinberger, Michaela; Jetten, Mike S. M.; Lücker, Sebastian; Wagner, Michael; Daims, Holger (Frontiers in Microbiology, 2017)
Nitrification, the oxidation of ammonia via nitrite to nitrate, has always been considered to be catalyzed by the concerted activity of ammonia- and nitrite-oxidizing microorganisms. Only recently, complete ammonia oxidizers (‘comammox’), which oxidize ammonia to nitrate on their own, were identified in the bacterial genus Nitrospira, previously assumed to contain only canonical nitrite oxidizers. Nitrospira are widespread in nature, but for assessments of the distribution and functional importance of comammox Nitrospira in ecosystems, cultivation-independent tools to distinguish comammox from strictly nitrite-oxidizing Nitrospira are required. Here we developed new PCR primer sets that specifically target the amoA genes coding for subunit A of the distinct ammonia monooxygenase of comammox Nitrospira. While existing primers capture only a fraction of the known comammox amoA diversity, the new primer sets cover as much as 95% of the comammox amoA clade A and 92% of the clade B sequences in a reference database containing 326 comammox amoA genes with sequence information at the primer binding sites. Application of the primers to 13 samples from engineered systems (a groundwater well, drinking water treatment and wastewater treatment plants) and other habitats (rice paddy and forest soils, rice rhizosphere, brackish lake sediment and freshwater biofilm) detected comammox Nitrospira in all samples and revealed a considerable diversity of comammox in most habitats. Excellent primer specificity for comammox amoA was achieved by avoiding the use of highly degenerate primer preparations and by using equimolar mixtures of oligonucleotides that match existing comammox amoA genes. Quantitative PCR with these equimolar primer mixtures was highly sensitive and specific, and enabled the efficient quantification of clade A and clade B comammox amoA gene copy numbers in environmental samples. The measured relative abundances of comammox Nitrospira, compared to canonical ammonia oxidizers, were highly variable across environments. The new comammox amoA-targeted primers enable more encompassing future studies of nitrifying microorganisms in diverse habitats. For example, they may be used to monitor the population dynamics of uncultured comammox organisms under changing environmental conditions and in response to altered treatments in engineered and agricultural ecosystems.